EFFECT OF MOLYBDENUM ADDITION AND BETA HEAT TREATMENT ON HYDROGEN RESISTANCE OF ZIRCALOY 4-0.5Y AT 600Â°C AND 800 TEMPERATURES - NURFALAH, AJI
The development of electrical energy sources that are lower in carbon emissions is a concern at this time. Development of nuclear power plants is one of the concerns for energy sources with lower carbon emissions, including in the development of the efficiency and safety of nuclear power. One of the important components in a nuclear reactor is the fuel cladding which is the support for nuclear fuel. Zirconium alloys are the main material of choice for fuel cladding because of their corrosion resistance, low neutron absorption, and good mechanical properties. Zircaloy-4 is a zirconium alloy that is widely used as a fuel cladding. One of the failures that are often experienced by zirconium alloys is hydrogen embrittlement, where hydride formation occurs by hydrogen penetration from corrosion products which can reduce the mechanical properties of the alloy. This research was conducted to analyze the effect of adding molybdenum and beta heat treatment on hydrogen resistance and mechanical properties of zircaloy 4-0.5Y-xMo alloy (x=0; 0.1; 0.4 wt%).